Faktor-Faktor yang Berhubungan dengan Kejadian Kekurangan Energi Kronik (KEK) Pada Ibu Hamil di Puskesmas Air Sugihan Jalur 25 Kabupaten OKI Tahun 2025 - Eka Dwiningsih; Intan Sari; Eka Rahmawati; Arie Anggraini (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2025)
Chronic Energy Deficiency (CED) is a condition where a pregnant mother experiences a chronic lack of food, resulting in health problems for the mother. The research aims to determine the factors related to the incidence of chronic energy deficiency (CED) in pregnant women in the Air Sugihan Jalur 25 Kabupaten OKI Community Health Center in 2025. This research design uses an analytical survey with a cross sectional method. The population in this study were all pregnant women in the Air Sugihan Jalur 25 Kabupaten OKI Community Health Center in 2025 from January - December 2025. The sample in this study was all pregnant women in the third trimester who had their pregnancies checked at the Air Sugihan Jalur 25 Kabupaten OKI Community Health Center in 2025 when this research was conducted in May - July 2025. The analysis technique uses Univariate, Bivariate (Chi square). Based on the results of the Chi Square statistical test, there is a partial relationship between age and the incidence of Chronic Energy Deficiency (KEK) in pregnant women in the Air Sugihan Jalur 25 Kabupaten OKI Community Health Center in 2025, the p value = 0.000. There is a partial relationship between knowledge and the incidence of Chronic Energy Deficiency ( KEK) in pregnant women in Air Sugihan Jalur 25 Kabupaten OKI Community Health Center in 2025 obtained a p value = 0.000. There is a relationship between family income and the incidence of Chronic Energy Deficiency (KEK) in third trimester pregnant women partially in the Air Sugihan Jalur 25 Kabupaten OKI Community Health Center in 2025 the value obtained p value = 0.000. It is hoped that the results of this research can be an illustration for the Air Sugihan Jalur 25 Kabupaten OKI Community Health Centerto further improve health services, especially services for checking the nutritional status of pregnant women in order to prevent incidents of Chronic Energy Deficiency (CED).